2012
DOI: 10.7461/jcen.2012.14.3.216
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic Results of Indirect and Combined Bypass Surgery for Adult Moyamoya Disease

Abstract: ObjectiveThe aim of this study was to compare the efficacy of indirect and combined bypass surgery for treatment of adult moyamoya disease (MMD). The definition of combined bypass surgery is a combination of superficial temporal artery-middle cerebral artery (STA-MCA) anastomosis and indirect anastomosis. Development of collateral circulation after surgery was investigated.MethodsForty three patients (58 hemispheres) with MMD were followed by cerebral angiography for at least six months after surgery, between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…10 Comparative analysis of cerebral angiography after revascularization has also shown that combined bypass results in increased development of collateral vessels when compared with various types of indirect revascularization alone. 6 Combined revascularization has been previously reported in the neurosurgery literature using a 2-to 3-cm wide strip of galea and/or temporalis muscle, in combination with low-flow STA bypass. We sought to improve the size and quality of the indirect component, as knowledge of axial arterial flaps allows the plastic surgeon to raise vascularized flaps in excess of 80 cm 2 , providing a theoretical advantage to the indirect revascularization territory size.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…10 Comparative analysis of cerebral angiography after revascularization has also shown that combined bypass results in increased development of collateral vessels when compared with various types of indirect revascularization alone. 6 Combined revascularization has been previously reported in the neurosurgery literature using a 2-to 3-cm wide strip of galea and/or temporalis muscle, in combination with low-flow STA bypass. We sought to improve the size and quality of the indirect component, as knowledge of axial arterial flaps allows the plastic surgeon to raise vascularized flaps in excess of 80 cm 2 , providing a theoretical advantage to the indirect revascularization territory size.…”
Section: Discussionmentioning
confidence: 98%
“…5 The development of collateral vasculature between vascularized tissue and the brain has been repeatedly demonstrated by angiography and autopsy. [6][7][8] Direct and indirect revascularization methods can also be combined for acute revascularization and delayed angiogenesis. 9 In an effort to improve outcomes, we have utilized a multidisciplinary approach with neurosurgery revascularization techniques and plastic surgery flap elevation techniques for combined revascularization procedures.…”
mentioning
confidence: 99%
“…They concluded that EDAGS can be a reliable alternative to combined bypass in adult MMD cases, however, they did not provide detailed information on the future stroke rate according to surgical method. Choi et al7) showed an improved revascularization angiographic outcome of combined bypass, than from indirect bypass, in adult MMD patients. In their study, a revascularization area of more than two-thirds of the MCA distribution was more frequently observed in the combined bypass group (n=12, 48.0%), than the indirect bypass group (n=9, 27.3%).…”
Section: Surgical Treatment Outcomesmentioning
confidence: 99%
“…The clinical manifestations include insufficient cerebral perfusion, transient cerebral ischemia, cerebral apoplexy, and epilepsy (Choi et al, 2012;Southerland et al, 2013). Focal neurofunctional deficit within the dominated region of the diseased blood vessels after cerebral ischemia severely affects the patients' quality of life.…”
Section: Discussionmentioning
confidence: 99%